Acute Exacerbation of Myasthenia Gravis with Topical Imiquimod Use. Issue 3 (1st July 2017) - Saad, Saadeddine; Mansouri, Bobbak; Housewright, Chad
Abstract : Imiquimod activates the immune system when applied to a local area. We report a patient with a history of well-controlled myasthenia gravis who was prescribed imiquimod for lentigo maligna. Treatment was halted after 2 weeks when the patient reported itching and irritating sensations in his throat, consistent with previous myasthenia exacerbations. The symptoms improved once imiquimod use was discontinued. We advise clinicians to be cautious when prescribing imiquimod to a patient with a history of myasthenia gravis.